Socio-cultural integration of Afghan refugees in Türkiye: the role of traumatic events, post-displacement stressors and mental health - Gülşah Kurt; Maryam Ekhtiari; Peter Ventevogel; Merve Ersahin; Zeynep Ilkkursun; Nuriye Akbiyik; Ceren Acarturk (Cambridge University Press, 2023)
Abstract Aims Socio-cultural integration of refugees has received scant attention in the academic literature. Türkiye hosts the largest number of refugees, including Afghans, as the second largest asylum-seeking group in Türkiye. There is a dearth of research into the mental health and integration of Afghan refugees in Türkiye. The aim of the present study was to investigate socio-cultural integration outcomes among Afghan refugees in Türkiye by considering the role of traumatic events and post-displacement stressors. The role of mental health in integration outcomes was further examined. Methods A cross-sectional, web-based survey study with 785 Afghan refugees in Türkiye was conducted between April and June 2021. Data were collected on socio-demographic characteristics, potentially traumatic events (PTEs) (Harvard Trauma Questionnaire), post-displacement stressors (Post-Migration Living Difficulties Checklist), mental health symptoms (Hopkins Symptoms Checklist-25), social integration- social bonds (contact with co-ethnic group members) and social bridges (contact with the host community)- and cultural integration (Vancouver Index of Acculturation). Structural equation modelling was conducted to test the hypothesized relationship between conflict and displacement-related stressors, mental health and socio-cultural integration. Results Findings showed that conflict-related traumatic events and post-displacement stressors significantly predicted higher mental health symptoms. Experiencing traumatic events significantly predicted higher levels of social bridges, adopting destination culture and lower level of maintaining heritage culture. Mental health problems predicted the relationship between stressors related to forced displacement and integration outcomes-social bridges and adopting destination culture. These findings highlight the role of mental health as an indispensable resource for socio-cultural integration. Further, conflict and displacement-related stressors are important determinants of socio-cultural integration among Afghan refugees in Türkiye. Conclusion Exposure to PTEs and post-displacement stressors were significant risk factors for the mental health and socio-cultural integration of Afghan refugees in Türkiye. These stressful experiences deteriorate refugees' mental health, which hinders their integration into the host society.